Coping styles and life satisfaction in adolescents from national educational institutions in the province of Huaral, 2014 - Verde Sevillano, Juri Janeth (2015)
This research aimed to establish the relationship between coping styles and life satisfaction among adolescents in national institutions of the province of Huaral. The random sample consisted of 258 adolescents from two national educational institutions; the level of education belongs to the 4th and 5th grade at the secondary level. The instruments used were the Coping Styles Questionnaire Carver COPE Scale and life satisfaction SWDS Dinner. The results showed that there is significant positive relationship with coping styles focused on the problem and emotion focused on satisfaction with life; negative and significant relationship with avoidant coping style and life satisfaction.